Screening in female patients for HPV and STI for early diagnosis of cervical cancer - Parasnis, Ketki; Palve, Tushar; Fatemi, Sakina; Narvekar, Rutuja; Miskin, Sneha; Bendale, Rucha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: High-risk human papillomaviruses (HPV) infection has been the most common sexually transmitted infection worldwide. Moreover, it is a necessary factor for the development of cervical cancer. Several studies have been carried out that screen HPV and other sexually transmitted infections (STI)s occurring in patients at the same time. Timely screening can help early diagnosis of pre-cancerous lesions and assist in prompt treatment to reduce mortality in such patients. The objective of the present study was to screen women for the presence of high-risk HPV (hrHPV) for the early diagnosis of cervical cancer. Some women were additionally screened for STIs. We also aimed to establish an association between the presence of HPV and STI. Methods: A total of 40 women aged 20-67 years participated in this study. Cervical and or vaginal swabs were collected in liquid-based cytology containers. The samples were tested for fourteen HPV genotypes by USFDA-approved Cobas HPV test. Out of these 40 women 26 were also tested for STI panel. Results: All women participants were screened for hr-HPV. A total 65% of the study population underwent both the HPV test and the STI test. 7.5% of total women were positive for hrHPV. 30.76% of women tested positive for Ureaplasma and Gardnerella vaginalis in the STI panel. Some women also showed simultaneous presence of STI and HrHPV. Conclusions: The results of this study will help in better and early diagnosis of women at risk of cervical cancer. The detection of HPV and STI present simultaneously can further help in establishing the role of these two conditions in the development of cervical cancer. Such studies are an encouragement to the HPV elimination programme and vaccination drive that has taken an impetus in recent times in India.